(untitled) (Studia Prawnicze / The Legal Studies, 1964)
The issue of differentiation between the scope of action of the administrative bodies and the scope of action of the judicial agencies has been placed against the backdrop of a broader problem, which is the differentiation between the scope of civil law and administrative law. It acquires special significance in relation to the agrarian law, which, if we keep in mind its current state in Poland in 1964, is a set of norms of administrative and civil laws imbued with the guiding idea of socialist restructuring the agrarian system, in particular restructuring the property relations as the norms of the agrarian law in the narrow sense, and the norms governing the organization in the agricultural production as the norms of the agrarian law in the broad sense. Due to the fact that the Polish legislation in the initial period of the agrarian reform (1944-1958) concentrated the implementation of resolutions on the agrarian reorganization in the hands of the state agrarian administration, this circumstance caused the spread of the difficult problem of the differentiation between the scope of both of these above branches of law to the area of the agrarian law. Thus, the correct solution of this issue is fundamentally reflected in stabilizing the positions of citizens participating in the agrarian reorganization. In addition, the lack of proper delimitation of competences of courts and administrative bodies in this area causes a confusion and inconsistency in points of view and decisions, violates the subject competence of the state bodies, undermines the rule of law and finally the foundations of law and justice. According to the author, the transfer of the right to implement the resolutions on the agrarian reorganization of 1944-1958 to the bodies (authorities) of the agrarian administration by the legislator does not follow exclusively from the fact of expanding the scope of the administration in a socialist state but has a goal, as the Supreme Court has emphasized in some of its rulings, to ensure the unity of the principles of this reorganization and state agrarian policy which dictates the concentration of all agrarian policies in the jurisdiction of the administrative bodies. As a result, the formation of the agrarian system on the basis of this group of resolutions has been taking place and is taking place to a large extent in the order of the directive action of administrative bodies through the administrative acts. If the courts intervened in cases of restructuring the agrarian system by resolving disputes in this area, they could not take into account the totality of relations and phenomena occurring in the course of agrarian reorganization with regard to each case of this kind and to the extent necessary to preserve the uniformity of this reorganization, despite the fact that they would also act together with public representatives — people’s assessors. Therefore, we have to state that the inadmissibility of trials in all civil cases continues to be relevant even if they are very indirectly and freely related to the first stage of agrarian reorganization, and the doubts that arise on this issue should be interpreted in favour of the competence of the administrative bodies. Moreover, according to the author, the inadmissibility of trials in the above cases is another particular feature of the agrarian law.